Light Aviation And Flight Safety: Monitoring System For Unpressurised Cabins. Physiological Parameters Monitorization - Sara Zorro; Andre Marques; Luís Patr\~ao; Jorge Silva; Miguel Castelo-Branco (European Regional Science Association (ERSA), 2012)
Light aviation pilots are exposed to many different environmental situations due to non-pressurized aircraft cabins. Those variations can push the human body to some limits, which associated with psychological factors may culminate in incidents or even fatalities. Really, a literature review on this theme suggests that a significant part of the incidents and fatalities within the light aviation that uses non-pressurized aircraft cabins are related to the human factor. This analysis might bring up a concealed but significant and worrying phenomenon in terms of flight safety: changes of pilot performance in the amendment of physiological parameters concerning to different pressure variations during the various flight stages. Flying is a reality that, although being used mostly for fast passenger and cargo transportation, also it is requested for leisure purposes by a very heterogeneous pool of pilots. This may be a concerning situation due to the disparity of human body (individual) reactions to flight conditions. Nature, both of environmental factors (like as pressure, temperature and humidity) or of human physiological behavior during different flight phases, is unpredictable. Therefore, it is very difficult to establish safety boundaries in this specific context. This work main objective is to analyze the influence of flight environmental conditions on pilot's physiological parameters and thus on tasks performance during different flight situations (or scenarios). In order to perform this analysis a portable and ergonomic monitoring system was built. This equipment records both the cerebral oximetry to study the phenomenon of hypoxia and its importance, and electrocardiography (ECG) and electroencephalography (EEG) parameters in order to establish a correlation among pressure variations, amount of mental workload, and several individual physiological parameters during different flight stages. The specific purpose of this study is how to define physiological limits for each pilot, calibrated through simulation tests contemplating different flight scenarios, in order to create in the next future a on board alert system to prevent possible incidents and fatalities. Also we suggest potential restrictions on European pilots licensing legislation for light aviation, based on some physiological boundaries, as a positive contribution to a safer flight environment.
Keywords: 330